Implementasi E-Commerce Berbasis Web pada Toko Denia Donuts Menggunakan Metode Prototype - Fenando Fenando (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The development of the internet and the implementation of technology that makes it easier for users to increasingly influence the business sector. Business people are starting to take advantage of the internet and technology to run their business or so-called E-Commerce. Denia Donuts Shop is an online shop that sells donuts in South Sumatera. The problems that occur, even though this store has marketed its products online, shop owners still use social media only in the process of transactions with consumers. This becomes very difficult when consumers want to make a purchase, consumers must send messages according to the format determined by the shop's owner, this method is made very difficult for consumers every time they make a purchase. On the other hand, the shop owner also finds it difficult to find product information, stock information, find out which consumers have bought during a certain period, and sales reports that are still recorded in a book. This article aims to build E-Commerce at Denia Donuts Shop that can help in marketing products widely and facilitate the process of transactions carried out by consumers. The system development method used is the prototype method. This research has resulted in an E-Commerce system that has been tested using the black box testing method and has been implemented in accordance with user requirements specifications.